2022
DOI: 10.1038/s41598-022-08470-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metallic trace elements contents in some major raw foodstuffs in Burkina Faso and health risk assessment

Abstract: Diet based on cereal, vegetables, oleaginous and dried fish are providing essential metallic elements. It can be also a source of exposure to toxic metallic elements. The aims of this study were to evaluate the contents on nine metallic trace elements (Fe, Zn, Mn, Co, Cd, Pb, Cu, Ni, Cr) in some major raw foodstuffs including rice, maize, peanut, tomato and dried fish in Burkina Faso and assess the health risk of these elements. Two hundred twenty-two samples were collected and analyzed by atomic absorption sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(31 reference statements)
3
1
0
Order By: Relevance
“…Only maize is below the maximum legal limit. Similar results were observed in Burkina Faso by Bazie et al [ 32 ] where Cd was detected in 92.5% of rice samples and in 44.44% of maize samples and more than half of the samples showed Cd concentrations above the limits set by the Codex Alimentarius. The abovementioned authors reported that the population of Burkina Faso is exposed to a non-cancer risk linked to metallic trace elements associated with rice, maize and peanut consumption [ 32 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Only maize is below the maximum legal limit. Similar results were observed in Burkina Faso by Bazie et al [ 32 ] where Cd was detected in 92.5% of rice samples and in 44.44% of maize samples and more than half of the samples showed Cd concentrations above the limits set by the Codex Alimentarius. The abovementioned authors reported that the population of Burkina Faso is exposed to a non-cancer risk linked to metallic trace elements associated with rice, maize and peanut consumption [ 32 ].…”
Section: Resultssupporting
confidence: 89%
“…Similar results were observed in Burkina Faso by Bazie et al [ 32 ] where Cd was detected in 92.5% of rice samples and in 44.44% of maize samples and more than half of the samples showed Cd concentrations above the limits set by the Codex Alimentarius. The abovementioned authors reported that the population of Burkina Faso is exposed to a non-cancer risk linked to metallic trace elements associated with rice, maize and peanut consumption [ 32 ]. The results of the present study are similar to those observed in Poland where Cd was found to have values of 0.27 ± 0.03; 0.2 ± 0.01; 0.31 ± 0.01 mg Cd/kg for maize, barley, and wheat, respectively [ 33 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, dietary intake of contaminated foods can also be a major route for entry of toxic chemicals into humans. This is particularly inevitable where food safety and quality are not rigorously monitored [ 2 , 3 ]. Maintaining food safety has remained a global challenge with public health implications and huge socioeconomic consequences.…”
Section: Introductionmentioning
confidence: 99%